Tree cover, patch structure and patch isolation correlate with patterns of Tufted Tit-Spinetail (Leptasthenura platensis) occurrence in Espinal forest remnants from east-central Argentina - Palacio, Facundo Xavier (2016)
The Tufted Tit-Spinetail (Leptasthenura platensis) is a common species from the southern Neotropical Region, but several ecological aspects, such as abundance patterns and habitat use, remain poorly known. I studied the relationship between Tufted Tit-Spinetail presence and characteristics of native forest patches (tree cover, patch area and interpatch distance) in eastern Buenos Aires province, Argentina. The probability of presence increased with tree cover and patch area and decreased with interpatch distance. Occurrence probability also decreased from summer to winter. Although Tufted Tit-Spinetail is not considered a species under threat, my results show that habitat features related to forest fragmentation are major factors explaining occurrence patterns in forest patches, and suggest that it would be a species sensitive to fragmentation.